TRACKING PERFORMANCE OF PNEUMATIC POSITION USING GENERALIZED MINIMUM VARIANCE CONTROLLER (GMVC) (Journal of Engineering and Health Sciences, 2019)
System modeling is an important task to develop a mathematical model that describes the dynamics of a system. The scope for this work consists of modeling and controller design for a particular system. Parametric approach using Auto Regressive with Exogenous input (ARX) model structure will be used to estimate the mathematical model or approximated model plant. In this research, the approximated plant model is estimated using System Identification approach. Once the mathematical model is obtained, Generalized Minimum Variance (GMV) controller are designed and simulated in MATLAB. Finally, a comparative study based on simulation is analyzed and discussed in order to identify which controller deliver better performance in terms of the system’s tracking performances.